POCUS Confirmation of Intraosseous Line Placement: Visualization of Agitated Saline within the Right Heart in a Critically Ill Infant - Inbar S.Y. Plaut; Zachary W. Binder (CINQUILL Medical Publishers Inc., 2023)
Intraosseous (IO) line placement can be a life-saving procedure in the management of critically ill patients.  Confirmation of correct IO line placement can be difficult. Prior studies have examined the use of point of care ultrasound (POCUS) to confirm IO line placement by using power Doppler over bone to detect flow within the intraosseous space. This case illustrates a novel use of POCUS in which agitated saline is visualized within the right heart as a means of confirming correct IO placement.